Professional Jurisdiction: an Exploration of the Police Experiences in Taking Indigenous Witness Statements - Zikalala, Nomsa Ingrid; Mofokeng, Jacob Tseko; Zenzile, Enoch; Motseki, Moses Morero (UIN Sunan Gunung Djati Bandung, 2024)
Research shows that the inaccurate translation of indigenous witness statements is a global phenomenon. This study was conducted to gain a better understanding of this phenomenon by exploring the experiences of South African Police Service (SAPS) members in taking indigenous witness statements. Using a qualitative method, interview schedules were administered to eighteen (18) SAPS members from nine Community Service Centres (CSC) in a township in the Gauteng province. Ethical considerations and measures of trustworthiness were applied to the study. Data were analyzed using Atlas.ti. The results showed that a majority of SAPS members reported there were no translators stationed at the designated CSCs, so they collaborated with colleagues to transcribe the indigenous witness statements into English. Five dominant themes emerged from the most regularly repeated responses: